Folate Targeted Solid Lipid Nanoparticles of Simvastatin for Enhanced Cytotoxic Effects of Doxorubicin in Chronic Myeloid Leukemia - Varshosaz, J.; Hassanzadeh, F.; Sadeghi, H.; Shakery, M. (Current Nanoscience, 2012)
Statins can inhibit growth of malignant cells. Aims: The aim of the present work was to increase efficacy of simvastatin on chronic meyloid leukemia K562 cells by folate targeted solid lipid nanoparticles (SLN). Methodology: Folate targeting agent was prepared by chemical reaction between folic acid and dodecylamine. Folate targeted SLNs of simvastatin were prepared by an emulsification- solvent evaporation method. Then cytotoxicity of SLNs was studied on K562 cell line by Trypan blue and cellular uptake by flow cytometry method. Different concentrations of doxorubicin were used in combination to SLNs of simvastatin to study their possible synergistic effect in reducing the required cytotoxic dose of doxorubicin. Results: Simvastatin loaded SLNs were more cytotoxic than free simvastatin. The targeting property of glyceryl monostearate (GMS) SLNs was more efficient than other studied lipids. SLNs of simvastatin could reduce the cytotoxic dose of doxorubicin particularly when the dose of doxorubicin was low. Conclusion: Folate targeted SLNs can significantly enhance cytotoxic effect of simvastatin on K562 cell line and show synergistic effect with doxorubicin in reducing its dose. This may be of great value from clinical point of view in reduction of the cardiac toxicity of doxorubicin.
Keywords: folate targeting